NATO's operation in Libya: Not a model for military interventions - Marco Overhaus (Stiftung Wissenschaft und Politik (SWP), 2011)
NATO's Operation Unified Protector in Libya has fostered the illusions of politicians and military planners that it is possible for outside powers to support regime change without the need to embark on counterinsurgency or externally driven state-building, which have consumed foreign troops and civilian aid agencies for many years. Yet it would be premature, and even dangerous, to consider Libya as a model for future military interventions. Developments in this country are unique in some important ways and they do not refute the central lesson that the international community has had to learn previously: Outside powers that engage in regime change in the first place need to be prepared to deal with a potentially very messy post-war phase. The operation in Libya has demonstrated how limited NATO member states' willingness and ability to actually prepare (and pay) for such a contingency has become
Keywords: 320